Recurrence of uveal malignant melanoma: a case report - Thapa, Madhu; Shrestha, GB; Sharma, AK; Karki, S; Khanal, S (Nepalese Journal of Ophthalmology, 2013)
Background: Malignant melanoma of uveal tract is a rare ocular malignancy. It is one of the significant causes of ocular morbidity and mortality which is less commonly seen in children. Case: We report an unusual case of orbital recurrence of malignant melanoma in a 14-yearold boy who had previously undergone enucleation of the left painful blind eye 8 months ago. He was diagnosed to have uveal malignant melanoma elsewhere which was confirmed by histopathology. Orbital recurrence was managed with modified exenteration with adjuvant chemotherapy and radiotherapy. Conclusion: In all treated cases of uveal melanoma, close follow up examination and monitoring is necessary for early diagnosis of the recurrence and to plan for further management. Nepal J Ophthalmol 2013; 5(10): 275-278 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8744